Seedless okra pod, chlorophyll, vitamin C and mineral content development using plant growth regulator in vitro and in vivo culture: Seedless okra pod, chlorophyll, vitamin c and mineral content - Hossain, ABM Sharif; Alenazi, Mekhled M Alenazi; Ahmed, Abu Saleh Ahmed; Alrudayni, Hassan A; Haouala, Faouzi; Al-Hashimi, Abdulrahman; Kahrizi, Danial; Alhudhaibi, Abdulrahman M (Cellular and Molecular Biology, 2023)
Vegetables are rich in vitamins, minerals and dietary fiber that keep a significant role in the functioning of the human body to refrain human health benefits. The experiment was carried out to investigate the effect of different concentrations of IAA on the seedless pod, chlorophyll, vitamin and mineral content of okra as human health benefits. The innovative seed soaking method of application using 0, 25, 50, 100 & 200 mg/l of IAA concentrations was used in okra before germination and cultured in vitro and in vivo. The lower concentrations (25 and 50 mg/l) of IAA significantly increased the pod setting compared to the higher concentration (100 and 200 mg/l). The higher concentration (100 and 200 mg/l) had lower fruit settings than the lower concentration (25 &50) had higher fruit settings. The higher pod size was obtained in the concentration of 100 & 200 mg/l of IAA (34.18 cm²) as compared to the control and other concentrations. In addition, the highest soluble solid content was obtained by 100 and 200 mg/l of IAA concentration as compared to the other concentrations. The maximum vitamin C was found in the concentration of 100 mg/l of IAA as compared to the control and other concentrations. Moreover, higher mineral contents like K, Ca, Mg, Na and Fe were found in 100 & 200 mg/l of IAA. The higher concentrations (100 and 200 mg/l) of IAA greatly increased the seedless okra percentage as compared to the lower concentration. It seemed that 100 and 200 mg/l concentration IAA was a better concentration for mineral content and seedless okra production as compared to the other concentrations.